1RS arm of Secale cereanum 'Kriszta' confers resistance to stripe rust, improved yield components and high arabinoxylan content in wheat - Szakács, Éva; Szőke-Pázsi, Kitti; Kalapos, Balázs; Schneider, Annamária; Ivanizs, László; Rakszegi, Marianna; Vida, Gyula; Molnár, István; Molnár-Láng, Márta (Scientific reports, 2020)
Wheat-rye T1BL.1RS translocation is widespread worldwide as the genes on 1RS arm have positive effect on stress resistance, grain yield and adaptation ability of wheat. Nowadays, the T1BL.1RS wheat cultivars have become susceptible to rust diseases because of the monophyletic ('Petkus') origin of 1RS. Here we report and discuss the production and detailed investigation of a new T1BL.1RS translocation line carrying 1RS with widened genetic base originating from Secale cereanum. Line '179' exhibited improved spike morphology traits, resistance against stripe rust and leaf rust, as well as higher tillering capacity, fertility and dietary fiber (arabynoxylan) content than the parental wheat genotype. Comparative analyses based on molecular cytogenetic methods and molecular (SSR and DArTseq) makers indicate that the 1RS arm of line '179' is a recombinant of S. cereale and S. strictum homologues, and approximately 16% of its loci were different from that of 'Petkus' origin. 162 (69.5%) 1RS-specific markers were associated with genes, including 10 markers with putative disease resistance functions and LRR domains found on the subtelomeric or pericentromeric regions of 1RS. Line '179' will facilitate the map-based cloning of the resistance genes, and it can contribute to healthy eating and a more cost-efficient wheat production.
Keywords: Secale; Plant Diseases; chromozomy rostlin; žito; Chromosomes, Plant; Translocation, Genetic; Disease Resistance; Triticum; pšenice; translokace genetická; geneticky modifikované rostliny; odolnost vůči nemocem; Plants, Genetically Modified; nemoci rostlin